Clinical significance of new oral anticoagulants in the prevention of thromboembolic complications in patients with atrial fibrillation: not all dreams come true - Yu. A. Bunin; S. V. Miklishanskaya (Столичная издательская компания, 2016)
Atrial fibrillation (AF) - is the most common tachyarrhythmia, which is diagnosed in 1-2% of the population. Non-valvular AF increases the risk of ischemic stroke in 5-7 times. More than 50% of thromboembolism originating from the heart is associated with non-valvular AF. Therefore, prevention of ischemic stroke and systemic embolism is one of the main aims of AF treatment. For a long time for prevention of them oral anticoagulants were used mainly from the group of vitamin K antagonists, most often warfarin. In connection with the known disadvantages of warfarin use, the elaboration of new oral anticoagulants (NOAC) became very important in clinical practice. The article presents a contemporary view of the advantages of the NOAC, indications and contraindications for their use. The international recommendations on their use in different clinical situations are analyzed. At the same time, the article deals with some questionable matters of antithrombotic therapy with NOAC at AF and authors give their point of view on a number of studies in the field of clinical arrhythmology. Currently, according to the authors, it is appropriate to speak of a differentiated approach to the appointment of the NOAC, that depends on a whole range of clinical factors, and the results of laboratory and instrumental investigations, rather than to compare these anticoagulants on the principle of "better or worse", as these estimates are not correct, and sometimes they are clearly far from the principles of medical ethics.